Proposição de um modelo de avaliação dos atributos de criação de valor na colaboração entre NPO e business - Soares, Felipe Alves de Oliveira (2018)
The number of non-profit organizations (NPO) has grown in the last decades in Brazil and has become important players in global politics, social, economic and non-business environment. Cross-sector partnerships and, in particular, business non-profit partnerships, have played an important role and it is considered by academics and professionals as an inescapable and powerful vehicle to create value for both partners. This dissertation aims to propose a multiattribute framework to evaluate the value creation in collaboration between NPOs and businesses. The Graphs Theoretical Approach was used to elaborate the framework. The Delphi method was used in order to determine the relationships among the attributes and the sub-attributes of value creation, so the framework can be applied to any kind of business nonprofit partnership. In order to validate the framework five organizations involved in this type of cross-sector partnership, where evaluated in the value creation perspective. As a result, it has been verified that the framework can be applied in any business non-profit partnership. Besides, it is flexible to insert other attributes and sub-attributes of value creation, considering the context of the partnership. The framework is able to quantify the qualitative aspects, generating an index of value creation, presenting a managerial decision-making tool that allows acting in the sub-attributes judged with a low or medium level of performance in the partnerships. By applying the framework, it was verified that the NPOs obtained a high level of value creation in the collaboration with the businesses, while the business obtained a medium level of value creation in their collaboration with NPOs. This research contributed to the advancement of knowledge about value creation in business non-profit partnerships. As the framework is generic, it can be applied in any type of partnerships between NPO and business, and it presents itself as a tool to support decision-making that can enhance the mutual benefits in the partnership.